SOCIAL PROTECTION OF PERSONS WITH DISABILITIES: THEORETICAL AND LEGAL PROBLEMS - Вишновецька, Світлана Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Review of the monograph by V.P.Melnik "Social protection of persons with disabilities: theoretical and legal problems". It is noted that the work is a comprehensive scientific research of the actual theoretical and practical problems of social protection of persons with disabilities, which includes a detailed comparative and legal analysis of the norms of the current national legislation in the field of social protection of persons with disabilities and leading countries of the world in connection with the intensification of intensive the integration process in recent years. Special attention is paid to the directions of implementation of the UN Convention on the Rights of Persons with Disabilities. It is concluded that V.P.Melnik’s monographic research has an undeniably significant value for the further development of science of social welfare law, performed at a high scientific and theoretical level, contains new scientifically-based results, which collectively solve a scientific problem, which consists in the development of conceptual the provisions of the theory of social protection of persons with disabilities.